Kajian Literatur Perbandingan Metode dan Dosis Demulsifier Dalam Mengatasi Emulsi Air-Minyak pada Minyak Mentah di Berbagai Wilayah - Trifena Tajeng; Baiq Maulinda Ulfah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The problem of air emulsion in crude oil is a significant challenge in the oil and gas industry because it reduces product quality and process efficiency. This study examined the effectiveness of demulsifiers on different types of crude oil by centrifugation and bottle test methods to separate water-oil emulsions. In Hassi Berkine crude oil, the REB09305 OS deemulsifier is effective at a low dose of 20 ppm with a 100% air discount at room temperature and centrifugation at 1200 rpm for 45 minutes. At the Main Oil Station (MOS) Menggung, the optimal dose of 200 ppm provided the lowest BS&W value of 1.6% using a combination of bottle test and centrifuge methods. In Bentayan oil, the B demulsifier with -OH group showed the best performance at a dose of 30 ppm and a temperature of 60°C with a BS&W of 0.1%. The use of a demulsifier according to specific doses and optimal conditions has been shown to improve the efficiency of emulsion indicators, reduce BS&W and salt content, and reduce the risk of corrosion.